Discussion, Part I: The Adult Analysis and Child Analysis Cases: Innate Influences versus the Impact of the External Influences of Separation and Divorce. Issue 1 (1st January 2019) - Straus, Robert B.
ABSTRACT: In Part I of his Discussion, Dr. Straus addresses the work of an adult analyst (Lament) and a child analyst (Bram) from the perspective of innate influences, external influences (the impact of parental separation and divorce), and their interrelationship. He refers to the parental separation and divorce in both of these cases as low conflict.